A Natural Way Of Boosting Immunity: The Role of Echinacea in Cold Prevention and Treatment - A Literature Review - Anna Ewa Zygmunt; Łukasz Karoń; Karolina Karoń; Wojciech Grabowski; Daria Pedrycz; Grzegorz Drapała; Emilia Pedrycz (Nicolaus Copernicus University in Toruń, 2024)
Echinacea, a widely used herbal remedy derived from the purple coneflower, is renowned for its potential benefits in treating and preventing the common cold. This review examines Echinacea's role in managing cold symptoms, its mechanisms of action, and its efficacy across various species and preparations. Echinacea species, particularly Echinacea purpurea, Echinacea angustifolia, and Echinacea pallida, contain active compounds such as alkamides, caffeic acid derivatives, polysaccharides, and glycoproteins, which contribute to its immunomodulatory, anti-inflammatory, and antiviral properties. Clinical studies demonstrate that Echinacea can modestly reduce the incidence, duration, and severity of colds, though results are variable due to differences in preparation forms (e.g., teas, tinctures, extracts) and study methodologies. Proprietary extracts like Echinaforce® have shown consistent benefits, while other formulations have yielded mixed results. Despite a generally favorable safety profile, including mild gastrointestinal disturbances and rare allergic reactions, the long-term safety, particularly in vulnerable populations, remains under-researched. Future research should focus on standardized formulations, detailed molecular mechanisms, and rigorous clinical trials to better define Echinacea's role in cold management. Overall, while Echinacea offers a promising option for cold prevention and treatment, its use should be informed by evidence-based practices considering formulation, dosage, and individual patient factors.